Longitudinal double-spin asymmetries for π0S in the forward direction for 510 GeV polarized pp collisions - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review, 2018)
The STAR Collaboration reports measurements of the longitudinal double-spin asymmetry, ALL, for neutral pions produced at forward directions in polarized proton-proton collisions, at a center-of-mass energy of 510 GeV. Results are given for transverse momenta in the range 2<pT<10 GeV/c within two regions of pseudorapidity that span 2.65<η<3.9. These results are sensitive to the polarized gluon parton distribution function, Δg(x), down to the region of Bjorken x∼10−3. The asymmetries observed are less than ±5×10−3 in magnitude and will help constrain the contribution to the spin of the proton from polarized gluons at low x, when combined with other measurements as part of a global analysis.
Gesehen am 05.07.2019